Halophyte adaptations in gray mangrove seedlings to salinity on the Persian Gulf coastline - Maryam Moslehi; Akram Ahmadi; Tom Pypker; Mohsen Dehghani Ghanatghestani; Majid Hassani; Mehrdad Zarafshar (Frontiers in Forests and Global Change)
This study aims to explore the salt tolerance mechanisms of Avicennia marina from the Persian Gulf, addressing the gap in understanding whether mangroves are facultative or obligatory halophytes. Seedlings were exposed to freshwater (control), low salinity (25% seawater), medium salinity (50% seawater), and high salinity (100% seawater) treatments for six months. The results revealed that medium salinity promoted optimal growth, with the highest values for plant height, root and shoot biomass, leaf area, and seedling vigor (2.86%). The non-salinity treatment showed lower vigor (1.96%) and greater leaf loss (17.96%). Medium salinity increased nitrogen and potassium levels, while high salinity elevated chloride and sodium content. Photosynthetic pigments were higher in moderate and low salinity treatments, and catalase activity peaked in freshwater, with peroxidase activity highest in both freshwater and high salinity treatments. These findings provide evidence that A. marina from the Persian Gulf is a facultative halophyte, capable of thriving in both saline and non-saline conditions, with salinity enhancing its growth and health.